Efficient total synthesis of sapinofuranone B - Kumar, P; Naidu, SV; Gupta, P (Journal of Organic Chemistry, 2005)
An efficient enantioselective synthesis of sapinofuranone B (1) using Sharpless asymmetric dihydroxylation, Sonogashira coupling, and Wittig olefination as the key steps is described.